Membangun Kualitas Produk, Strategi Harga Dan Kualitas Pelayanan Terhadap Kepuasan Yang Berdampak Pada Loyalitas Konsumen Pada Apotek Asahi Farma Sragen - Muslih Abdul Hamid; Aris Tri Haryanto (STIE AUB Surakarta, 2025)
The aim of this research is to empirically test and analyze efforts to build product quality, price strategy and service quality on satisfaction which has an impact on consumer loyalty at the Asahi Farma Sragen Pharmacy. The population in this research were consumers at the Asahi Farma Sragen Pharmacy, totaling 500 consumers in the first week of October 2023. The sample taken in this research was 20% of the population of 500, namely 100 respondents in order to get better results. The sampling technique is random sampling. The analysis technique used is the path analysis test. The research results show that product quality has a positive and significant effect on consumer satisfaction. Pricing strategy has a positive and significant effect on consumer satisfaction. Service quality has a positive and significant effect on consumer satisfaction. Product quality has a positive and significant effect on consumer loyalty. Pricing strategy has a positive and significant effect on consumer loyalty. Service Quality has a positive and significant effect on Consumer Loyalty. Consumer satisfaction has a positive and significant effect on Consumer Loyalty. The results of the simultaneous test (F test) in the second equation show that the value of F = 99.208 with a significance level of 0.000 < 0.05, so it can be concluded that together the independent variables have a significant effect on consumer loyalty. The total R2 value of 0.718 can be interpreted as consumer loyalty at Asahi Farma Sragen Pharmacy, explained by the variables product quality, price strategy, service quality and consumer satisfaction of 71.8%. Product quality is the most dominant variable in increasing consumer loyalty at Asahi Farma Sragen Pharmacy. The direct influence of product quality on consumer loyalty is greater than the indirect influence, so increasing consumer loyalty is more effective through direct channels on product quality variables. The direct influence of pricing strategy on consumer loyalty is greater than the indirect influence, so increasing consumer loyalty is more effective through direct channels on the price strategy variable. The direct influence of service quality on consumer loyalty is greater than the indirect influence, so increasing consumer loyalty is more effective through direct channels.